Rapid Orientation of Students for Emergency Remote Learning during the Covid‑19 Lockdown (Journal of Student Affairs in Africa, 2021)
In response to the spread of the Covid‑19 pandemic, the President of South Africa declared a national lockdown that commenced on 27 March 2020. This posed numerous challenges to the higher education sector, one of which was the preparation of students forced to stay at home to be able to study remotely under unique and often unfavourable circumstances. This article outlines and reflects on the conceptualisation, development, and implementation of an online orientation programme aimed at preparing students to rapidly move to emergency remote learning as a result of a nationwide lockdown. Teaching and Learning Centre staff in the Faculty of Commerce, Law and Management at a South African university rapidly created a short online orientation programme in the institutional Learning Management System, using Salmon’s five-stage model as a conceptual framework. The objective was to enable students to acquire the skills and knowledge required for continuing with the university academic programme from 20 April 2020 via emergency remote learning. The orientation programme covered the priority areas of how to get started in emergency remote learning, broad study skills, how to use the required technologies for learning, and managing personal well‑being during social isolation and emergency remote learning. In this article, the conceptualisation and development of the orientation programme is analysed, before reflecting on its implementation, challenges, mitigating measures, and lessons learned. Feedback from students indicates that the majority of students felt more prepared for continuing the academic programme, although they still reported feeling anxious about the many uncertainties. The intervention emerges as a useful strategy for helping students transition during a crisis and contributes to the understanding of how to prepare students for rapid transition to Emergency Remote Learning.
Keywords: Covid‑19; emergency remote learning; orientation programme; student orientation; student success; student support